2020
DOI: 10.3390/toxins12110683
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylformamide Inhibits Fungal Growth and Aflatoxin B1 Biosynthesis in Aspergillus flavus by Down-Regulating Glucose Metabolism and Amino Acid Biosynthesis

Abstract: Aflatoxins (AFs) are secondary metabolites produced by plant fungal pathogens infecting crops with strong carcinogenic and mutagenic properties. Dimethylformamide (DMF) is an excellent solvent widely used in biology, medicine and other fields. However, the effect and mechanism of DMF as a common organic solvent against fungal growth and AFs production are not clear. Here, we discovered that DMF had obvious inhibitory effect against A. flavus, as well as displayed complete strong capacity to combat AFs producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
1
10
0
Order By: Relevance
“…Analysis of the coregulatory gene expression network under conditions with and without AF production occurring showed that the expression levels of genes involved in the TCA cycle and glycolysis were significantly reduced in the non-aflatoxigenic conditions . Pan et al showed that dimethylformamide inhibition of AFB1 biosynthesis may be due to downregulation of pathways related to the TCA cycle and glycolysis . Here, our multiomics, qRT-PCR, and 13 C-glucose parallel labeling results together revealed that AL promoted the TCA cycle.…”
Section: Discussionsupporting
confidence: 60%
“…Analysis of the coregulatory gene expression network under conditions with and without AF production occurring showed that the expression levels of genes involved in the TCA cycle and glycolysis were significantly reduced in the non-aflatoxigenic conditions . Pan et al showed that dimethylformamide inhibition of AFB1 biosynthesis may be due to downregulation of pathways related to the TCA cycle and glycolysis . Here, our multiomics, qRT-PCR, and 13 C-glucose parallel labeling results together revealed that AL promoted the TCA cycle.…”
Section: Discussionsupporting
confidence: 60%
“…These results suggested that the deletion of sfgA may affect the main components of the fungal cell wall of A. flavus , including chitin and structural polysaccharides. Consequently, the cells will generate a defensive response to by over-expressing alpha-1,3-glucan synthase genes to overcome stimulation [ 59 ]. In general, it is possible that the response of sfgA to environmental stress resistance could be linked to the differential expression of these genes.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, methyl oleate's reduced fungal toxicity may be partly explained by its higher log P value of 7.45 (Table 4). According to hazard identi cation and ecotoxicity values, methyl oleate (commonly known as biodiesel) is regarded nonhazardous and less harmful than other hazardous solvents such as DMF (Pan et al, 2020). (Table 4).…”
Section: Discussionmentioning
confidence: 99%